PROMOTING NEW LITERACIES IN SCHOOLS: A proposition to integrate digital literacy in pre-service teacher education - Rahmat Yusny (Jurnal Ilmiah Didaktika, 2017)
This paper renders a preposition to integrate Digital Literacy into Pre-service teacher education programs in universities and various teacher trainings. The current emergence of high dependence toward digital technology demands teacher education programs to make contribution in order to educate and prepare pre-service teachers to overcome issues related to negative impacts of digital technology. 21st century skills are amongst the core requirement for advanced human resources living in this era. Teacher education curriculum must be able to accommodate sufficient knowledge and resources to enable students becoming digital literate society. As what depicted today among our society, very little attention given toward the way using internet technology securely and politely. Beginner adopters of technology are now spoon fed with very user friendly gadgets and apps that often neglect to learn about effects and impacts the technology caused. In addition, although it still can be argued, often most of the marvels do not really foster productivity for these groups of technology users. Therefore, proposition to raise awareness among pre-service teacher in is emphatically needed.